Influence of Songs in Primary School Students' Motivation for Learning English in Lima, Peru - Aguirre, Diego (2016)
Many studies have shown that using music and songs while learning a new language can be of great benefit to students in aspects such as grammar, pronunciation and vocabulary. However, the use of songs in class as motivation to learn English is a subject that has not been explored thoroughly. The purpose of this study is to explore how the use of songs in English helps motivating students while learning English as a Second Language (ESL). The participants were primary school students at a private school located in the Lima Metropolitan Area. This study used a mixed-method design that included observations carried out by the research team and questionnaires completed by students. The results show that students are motivated to participate and become more engaged in classroom activities when songs are used in their English classes. This result was more strongly confirmed with the observations than with the questionnaires.